A Guide to Functional Analytic Psychotherapy Awareness, Courage, Love, and Behaviorism - Tsai, Mavis; Kohlenberg, Robert J.; Kanter, Jonathan W.; Kohlenberg, Barbara; Follette, William C.; Callaghan, Glenn M.; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
"In 1991 Functional Analytic Psychotherapy (FAP) was among the first new approaches that proved that behavioral psychology could be brought more fully and effectively into psychotherapy. In this long awaited volume, leaders in FAP show how the model has developed and provide guidance for its clinical implementation. Alone and in combination with other treatments, FAP speaks to some of the deepest clinical issues there are, and can empower clinical work virtually regardless of the clinician's current approach. Highly recommended." -Steven C. Hayes, Ph.D., University of Nevada "Functional Analytic Psychotherapy offers the best opportunity for the development of genuinely integrative therapeutic practice the field has ever seen. This guidebook to FAP should help to open up new exciting vistas to therapists of all theoretical persuasions. It is one of the most important books on psychotherapy in decades." -Alan S. Gurman, Ph.D., University of Wisconsin School of Medicine and Public Health "This volume describes an approach to therapy that creatively highlights the use of the therapy interaction as a sample of the client's problematic interpersonal relationships. Using an integrative blending of learning principles with sound clinical interaction skills, Functional Analytic Psychotherapy helps clients to learn what does and what does not get them what they want and need. All this is richly illustrated with case materials and therapy transcripts, providing the clinician with clear guidelines on how to implement this approach to therapy." -Marvin R. Goldfried, Ph.D., Stony Brook University For more than two decades, Functional Analytic Psychotherapy has brought new meaning, depth and intensity to client-therapist relationships by focusing on the subtle ways clients$1 (Bdaily life problems occur in the therapy session. FAP$1 (Bs nuanced, curative power can help clients with issues as varied as depression, anxiety, intimacy difficulties, personality disorders, problems of the self, substance abuse and OCD to move beyond their symptoms and into their passion for living and loving. In A Guide to Functional Analytic Psychotherapy, originators Mavis Tsai and Robert Kohlenberg join with other FAP practitioners to present a conceptual framework and treatment innovations that take readers through the deep complexities and possibilities of the therapeutic bond. This book also underscores how attention to mindfulness and the self makes maximum clinical use of the uniqueness of every client$1 (Band every therapist. Highlights of the Guide: The five core principles of therapeutic technique. Empirical underpinnings of FAP interventions. Case studies and transcripts of assessment procedures and therapy sessions. Examples of how to use FAP alone and in combination with other therapies. Illustrations of the course of FAP, from the initial session to the end of therapy. Therapist self-development and supervision issues. Inspiring clients to improve society: the practice of "green FAP." Appendix of questionnaires, feedback forms, and other essential FAP tools. As this transformative therapy continues to grow in influence, A Guide to Functional Analytic Psychotherapy will be a vital, practice-enhancing reference for clinicians and graduate students.s
What is Functional Analytic Psychotherapy? -- Lines of Evidence in Support of FAP -- Assessment and Case Conceptualization -- Therapeutic Technique: The Five Rules -- Self and Mindfulness -- Intimacy -- The Course of Therapy: Beginning, Middle and End Phases of FAP -- Supervision and Therapist Self-Development -- Values in Therapy and Green FAP.
Keywords: Psychology; Psychiatry; Clinical psychology; Psychology; Clinical Psychology; Psychiatry; Electronic books